De Hongaarse galeislaaf-predikanten en Nederland - Bujtás, László Zsigmond (Acta Neerlandica, 2026)
The Hungarian protestant ministers who had been baselessly charged in 1673 and 1674 bya special court at Pressburg with rebellion, treason and defamation of the Catholic Churchwere sentenced to death. Those who converted to Catholicism or promised to leave thecountry could escape. Those who persisted were sold at Naples to Spanish galleys asslaves. The ministers asked help, among others, from the Netherlands. As a result of effortsof many persons the States General instructed in November 1675 admiral Michiel deRuyter to liberate the galley slaves. After their liberation in February 1676, they were inexile in Zürich. Eight of them visited the Netherlands in the autumn of that year to try toget diplomatic and financial support so that they could return to Hungary in order tocontinue their ministry. The Netherlands helped them a lot in both areas. Lots of booksdealt with their story in the 17th and 18th centuries in the Netherlands. Later they becamemore and more part of the memory place ‘Michiel de Ruyter’.